2005
DOI: 10.1017/s1472928805000063
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical dysrhythmia syndrome: MEG imaging of neuropathic pain

Abstract: Abnormal thalamocortical dynamics have been proposed as the underlying mechanism for a subset of neurological and psychiatric disorders that include centrally generated pain. Spectral analysis and independent component-based localization of neuromagnetic signals reveal ongoing theta-range activity localized to physiologically significant cortical regions in a group of subjects with well-characterized central and peripheral lesions. In addition, recordings from subjects who failed to obtain relief from spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 47 publications
9
42
1
4
Order By: Relevance
“…Previous studies [28][29][30] have related the clinical phenomenon of chronic neuropathic pain to an increase in low-and high-frequency spectral EEG and magnetoencephalography activities. This correlation is further supported by the evidence of reduced theta overactivity in the EEG recordings of patients treated with CLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [28][29][30] have related the clinical phenomenon of chronic neuropathic pain to an increase in low-and high-frequency spectral EEG and magnetoencephalography activities. This correlation is further supported by the evidence of reduced theta overactivity in the EEG recordings of patients treated with CLT.…”
Section: Discussionmentioning
confidence: 99%
“…The mean spectral band power was calculated from 1-48 Hz. Spectral bands were defined as follows: delta (2-4 Hz), theta (4-8 Hz), alpha1 (8-13 Hz), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). (Note that the superior spectral band limit is included only in the next higher band.)…”
Section: Quantitative Eeg Proceduresmentioning
confidence: 99%
“…Recent studies have identified a relationship between severe neurogenic pain and the presence of a specific EEG pattern called thalamocortical dysrhythmia (TCD) [19][20][21][22]. Sarnthein et al [23] compared the EEG spectrum of 15 patients with severe chronic pain with matched healthy controls, and found marked differences both with respect to the power in the theta and beta domains and in the frequency of the peak of the power spectral density.…”
Section: Introductionmentioning
confidence: 99%
“…These bursts were described in vitro and in vivo and related to a state of membrane hyperpolarization (Llinás and Jahnsen 1982;Steriade et al 1997). This enhanced theta thalamic activity found a correlate in local field potentials, EEG and MEG studies (Llinás et al 1999;Moazami-Goudarzi et al 2010;2008;Sarnthein and Jeanmonod 2008;Sarnthein et al 2006;Schulman et al 2005;Stern et al 2006). Evidence for the role of the medial thalamus in NP came already from clinical studies in the late forties (Hécean et al 1949), since it was demonstrated that in contrast to all other lesional surgeries, medial thalamotomies against NP provide a good success rate, produce no somatosensory or other deficits, and have a low complication rate, with especially the absence of risk for the development of iatrogenic pain (Jeanmonod et al 1994;Jeanmonod and Morel 2009;Sano 1977).…”
Section: Pathophysiological Mechanisms For Npmentioning
confidence: 88%
“…Many studies using imaging and electrophysiological techniques have examined the cortical and subcortical representation of pain (Bingel et al 2002;Buchel et al 2002;Garcia-Larrea et al 2003;Petrovic et al 2004;Ploner et al 2002;Shibasaki 2004;Treede et al 2003) and NP (Hsieh et al 1995;Llinás et al 1999;Shulman et al 2005;Walton et al 2010;Willoch et al 2000;Wydenkeller et al 2009). Electroencephalography (EEG) and magnetoencephalography (MEG) studies have shown that NP is associated with increased low (theta: 4-7 Hz and alpha: 8-13 Hz) and high (beta: 13-30 Hz) frequency band power (Boord et al 2008;Llinás et al 1999;Sarnthein et al 2006;Schulman et al 2005;. These spectral power increases occurred in all cortical partners of the above-mentioned nociceptive pain matrix, so that a NP matrix globally identical with it may be proposed ).…”
Section: Introductionmentioning
confidence: 99%